One- and two-photon absorption properties of quadrupolar thiophene-based dyes with acceptors of varying strength - Canola, Sofia (Photochem Photobiol Sci, 2019)
The one-photon (1P) and two-photon (2P) absorption properties of three quadrupolar dyes, featuring thiophene as donor and acceptors of varying strength, are determined by a combination of experimental and computational methods employing density functional theory (DFT). The emission shifts in different solvents are well reproduced by time-dependent DFT calculations with the linear response and state specific approaches in the framework of the polarizable continuum model. The calculations show that the energies of both 1P- and 2P- active states decrease with an increase of the strength of the acceptor. The 2P absorption cross-sections predicted by response theory are accounted for by considering just one intermediate state (S(1)) in the sum-over-states formulation. For the chromophore featuring the stronger acceptor, the energetic positions of the 1P- and 2P- active states prevent exploitation of the theoretically predicted very high 2P activity due to the competing 1P absorption into the S(1) state.